ChemInform Abstract: Asymmetric Total Syntheses of the trans‐2‐Aryl‐6‐alkyltetrahydropyrans Diospongin B and Parvistones D and E from a Common Precursor. Issue 43 (7th October 2016) - Li, Zhilong; Tong, Rongbiao
Abstract: The strategy of the asymmetric total synthesis features a high‐yielding three‐step reaction sequence: Achmatowicz rearrangement, reductive γ‐deoxygenation, and Matsuda—Heck coupling to construct the rare and challenging trans‐2‐aryl‐6‐alkyltetrahydropyrans, which serve as common intermediates for the syntheses of diospongin B (I), and parvistones D (II) and E (III).